ANALISIS PENGARUH JENIS NYERI DADA TERHADAP RATA-RATA TEKANAN DARAH DAN USIA MENGGUNAKAN MANOVA - Helvy Tiana Rosa Nabila; Annisa’ Riskika Hayyu; Sri Pingit Wulandari (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2024)
This study aims to analyze the effect of chest pain type on mean blood pressure and age using the Multivariate Analysis of Variance (MANOVA) method. Chest pain is a common symptom that can indicate various health conditions, including heart disease. The data used in this study was taken from the "Heart Failure Prediction ” dataset downloaded from Kaggle, which included variables such as chest pain type, blood pressure, and patient age. MANOVA analysis was performed to test whether there were significant differences in blood pressure and age based on the type of chest pain (Typical Angina, Atypical Angina, Non-Anginal Pain, and Asymptomatic). MANOVA test results showed that at least one type of chest pain significantly affected blood pressure and age. Multiple comparison tests were conducted to identify differences between chest pain groups. This study concluded that chest pain type significantly affected blood pressure, but no significant difference was found in age based on chest pain type. These findings may help in the diagnosis and management of patients with chest pain, and provide important information for the prevention of cardiovascular complications.